Representing Identity In Cinema: The Case Of Selected Independent Films Of Bangladesh - Hoque, Md. Fahmidul (2010)

(untitled)
In the contemporary post-colonial, globalised and post-9/11 era, the question of national identity has emerged as a significant one. This explorative study tends to examine how the Bengali Muslim identity i.e. the national identity of Bangladesh, is represented in selected independent films. The key objective of the study is to examine how national identity is represented in selected independent films made by four leading independent filmmakers – Abu Sayeed, Tanvir Mokammel, Morshedul Islam and Tareque Masud. Theoretical applications of national identity by Earnest Gellner, Benedict Anderson, Arjun Appadurai, Homi K Bhabha and Stuart Hall and the notion of representation by Stuart Hall are instructive here in guiding this study. For textual analysis of selected films, film narratology derived from the theory of Narrative Discourse by Gerard Gennette has been applied. Also the idea of cultural institution is used to relate to the topic to the larger cultural, historical and societal aspects. The method of the study is qualitative and the measures of the study are in-depth interviews and analyses of film texts. The analyses find the independent filmmakers of Bangladesh try to depict Bengaliness, the ethno-linguistic identity approach, as the preferred identity approach of Bengali Muslims and portray Muslimness, the religious identity and popular religion identity approach, as the ‘other’ identity. The findings also suggest that to sustain the ethnic and cultural elements of Bengaliness on the screen, directors do not hesitate to orientalise themselves to the interests of the global audience. The study finds independent cinema of Bangladesh as an influential cultural institution in portraying national identity. This study contributes to the understanding of the identity debate and diversity prevailing in the society. This, in turn, it helps resolving discussion on contesting of identity approaches and contributes to the development of society, polity and nationhood as well as generate new knowledge in Asian cinema and national cinema within the global discipline of cinema studies.